Cervical cancer screening management practices and prevention in uMsunduzi Local Municipality primary care clinics - Bhekuyise L. Mncube; Sipho W. Mkhize (AOSIS, 2022)
Background: Although cervical cancer is preventable, it remains the most feared and second most common cancer in women worldwide, as well as the leading cause of cancer deaths in many low- and middle-income countries, including South Africa. Numerous studies conducted globally, in Africa and in South Africa revealed a knowledge gap about cervical cancer and its preventive strategies, including cervical cancer screening, among nurses and the general population. Aim: The purpose was to investigate and describe nurses' knowledge and management practices regarding cervical cancer screening in uMsunduzi Local Municipality, KwaZulu-Natal. Methods: The study was directed by a positivism paradigm. A quantitative research approach and nonexperimental descriptive design was used in this study. Probability random sampling was used, and a self-administered questionnaire was used to collect data. Eighty-three professional nurses participated in the study. Results: The study discovered that professional nurses working in selected clinics in uMsunduzi Local Municipality, KwaZulu-Natal, had a high level of knowledge about cervical cancer and its screening. Nonetheless, despite the high level of knowledge demonstrated, the level of practice remained low. Conclusion: Cervical cancer morbidity and mortality have long been a major health concern in South Africa's general population. The study found that PNs are knowledgeable about cervical cancer screening; conversely, practice was low. This paper includes recommendations for future research, nursing practice, nursing education and the Department of Health. Contribution: This study contributed vastly to the body of knowledge in managing cervical cancer screening practices, particularly in health promotion and prevention of diseases at primary care level.